Vps26B‐retromer negatively regulates plasma membrane resensitization of PAR‐2. (15th July 2015) - Bugarcic, Andrea; Vetter, Irina; Chalmers, Silke; Kinna, Genevieve; Collins, Brett M.; Teasdale, Rohan D.
Abstract Retromer is a trimeric complex composed of Vps26, Vps29, and Vps35 and has been shown to be involved in trafficking and sorting of transmembrane proteins within the endosome. The Vps26 paralog, Vps26B, defines a distinct retromer complex (Vps26B‐retromer) in vivo and in vitro. Although endosomally associated, Vps26B‐retromer does not bind the established retromer transmembrane cargo protein, cation‐independent mannose 6‐phosphate receptor (CI‐M6PR), indicating it has a distinct role to retromer containing the Vps26A paralog. In the present study we use the previously established Vps26B‐expressing HEK293 cell model to address the role of Vps26B‐retromer in trafficking of the protease activated G‐protein coupled receptor PAR‐2 to the plasma membrane. In these cells there is no apparent defect in the initial activation of the receptor, as evidenced by release of intracellular calcium, ERK1/2 signaling and endocytosis of activated receptor PAR‐2 into degradative organelles. However, we observe a significant delay in plasma membrane repopulation of the protease activated G protein‐coupled receptor PAR‐2 following stimulation, resulting in a defect in PAR‐2 activation after resensitization. Here we propose that PAR‐2 plasma membrane repopulation is regulated by Vps26B‐retromer, describing a potential novel role for this complex.